STUDI DESKRIPTIF MENGENAI MOTIVASI BELAJAR PADA SISWA SMA NEGERI 1 CISARUA - Resi Fatonah; Heris Hedriana; Ecep Supriatna (IKIP Siliwangi, 2021)
This study aims to determine the level of learning motivation in students of SMA Negeri 1 Cisarua, West Bandung Regency. The research conducted by the researcher is a quantitative research, while the method used is a quantitative descriptive method. Methods of data collection using a questionnaire, and study documentation. Data analysis with percentage technique, correlation with the help of SPSS for Windows version 20.0 program. Based on the results of research and discussion in this study, the following conclusions can be drawn. From the results of the equation formed, it can be explained that there are 20% of students whose learning motivation is low, 59% moderate and 21% high.Keywords: Learning Motivation, Students